Multidimensional insights into the biodiversity of Streptomyces in soils of China: a pilot study - Ziguang Deng; Wei Yang; Tongtong Lin; Yaohai Wang; Xiaojing Hua; Xiaoyu Jiang; Junhao Chen; Dan Liu; Zhiqiang Ye; Yu Zhang; Michael Lynch; Hongan Long; et al. (Microbiology Spectrum)
ABSTRACT Streptomyces, a diverse group of filamentous bacteria found predominantly in soil, play a crucial role in nutrient cycling and produce many valuable secondary metabolites for the pharmaceutical industry. In this pilot study, we collected 19 soil samples from 14 provinces in China to preliminarily investigate the biodiversity and genetic structure of Streptomyces in soils of China from different dimensions, using recently developed cost-efficient amplicon and whole-genome library preparation methods. Amplicon analysis showed that Actinobacteria were among the most abundant bacteria, with 0.3% of amplicon sequence variants (ASVs) belonging to Streptomyces. Meanwhile, we successfully isolated 136 Streptomyces natural strains and assembled their genomes, including 26 previously unreported species, underscoring the need for further exploration of soil Streptomyces in China. Population genetics analysis revealed that homologous recombination may primarily drive the extensive genetic diversity observed in Streptomyces, as well as a complex population structure. Complementing this, pan-genome analysis shed light on gene diversity within Streptomyces and led to the discovery of rare genes, further emphasizing the vast genetic diversity of this genus. Additionally, multiple metabolic gene clusters were found in these Streptomyces strains, as well as some potentially unique or uncommon ones were found. These findings not only highlight the biological and metabolic diversity of Streptomyces but also provide a technical framework for future studies on the global biodiversity and evolution of this genus.IMPORTANCEStreptomyces, a prominent group of Actinobacteria, holds significant importance in ecosystems and biotechnology due to their diverse array of metabolic products. However, research on the biodiversity of soil Streptomyces across extensive geographical scales in China has been limited, and their genetic diversity has rarely been evaluated using modern population genetics principles. This pilot study successfully addresses these gaps by conducting a preliminary exploration on the biodiversity of Streptomyces in Chinese soils from multiple perspectives, providing valuable insights for a deeper understanding of their biodiversity and a novel technical framework for future large-scale explorations of its diversity.